Toxocariasis and Public Health: An Epidemiological Review - Anunobi Toochukwu Joy; Okoye Ikem Chris; Nwosu Chigozie Godwin (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2017)
An epidemiological review of toxocariasis aimed to underpin its prevalence, proclivity and prognosis was undertaken. Human toxocariasis constitutes one of the most common parasitic infections worldwide, which is more prevalent in developing and tropical countries. Human infection is caused by ingesting the eggs which were shed in the faeces of the defi nite dog or cat host. There is a range of clinical manifestations of toxocariasis in human, but the two classical clinical syndromes often described are visceral and ocular larva migrans. The clinical signs and complications which result from infection with this parasite are mostly dependent on the number and migration locations of Toxocara larvae. Visual identifi cation of larvae in tissues and organs is the gold standard for toxocariasis diagnosis in human, while an enzyme linked immunosorbent assay detecting Imunoglobulin-G antibodies against Toxocara excretory-secretory antigen is the reference test for immunodiagnosis. In human, loss of vision, hypereosinophilia, encephalitis and problems involving the liver, lung and the central nervous system are the most important complications. Poor hygiene, poverty and lack of education can exacerbate the exposure to Toxocara infection. Albendazole is the treatment of choice for toxocariasis. Conclusively, the present review recommends that regular stool examination and frequent chemotherapy of pets can be effective in reducing the egg number deposited in soil; reducing the number of pet animals or limiting contacts of small children with them and good hygiene practices will limit transmission of toxocariasis.